2019
DOI: 10.1039/c9em00101h
|View full text |Cite
|
Sign up to set email alerts
|

Mycoremediation of petroleum contaminated soils: progress, prospects and perspectives

Abstract: A review on mycoremediation of petroleum-contaminated soils to identify developments, limitations and perspectives for its optimal utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 70 publications
0
17
0
1
Order By: Relevance
“…The susceptibility of hydrocarbons to be degraded by microorganisms (linear alkanes > branched alkanes > small aromatic compounds > cyclic alkanes > polycyclic aromatic hydrocarbons) is one of the limiting factor for biodegradation. Soil fungi have been reported with efficiency of biodegradation of 6% to 82% while soil bacteria [2] and marine have biodegradation efficiency of 0.13-50% and 0.003-100% respectively [3]. The fungal oxidation of hydrocarbon compounds employees' monooxygenase enzyme that leads to formation of trans-diol.…”
Section: Introduction B a C K G R O U N Dmentioning
confidence: 99%
“…The susceptibility of hydrocarbons to be degraded by microorganisms (linear alkanes > branched alkanes > small aromatic compounds > cyclic alkanes > polycyclic aromatic hydrocarbons) is one of the limiting factor for biodegradation. Soil fungi have been reported with efficiency of biodegradation of 6% to 82% while soil bacteria [2] and marine have biodegradation efficiency of 0.13-50% and 0.003-100% respectively [3]. The fungal oxidation of hydrocarbon compounds employees' monooxygenase enzyme that leads to formation of trans-diol.…”
Section: Introduction B a C K G R O U N Dmentioning
confidence: 99%
“…Fungal soil remediation is still less studied than bacterial hydrocarbon degradation processes [10]. Fungi might be more advantageous over bacteria in the remediation process as they do not depend on merely soluble, readily absorbed organic compounds for nutrition [11]. The use of fungi for air biofiltration has also been investigated in recent years [12].…”
Section: Introductionmentioning
confidence: 99%
“…Yet these techniques have not been utilised commercially in many tropical regions. Dickson et al (2019) reported that for optimal utilisation of these techniques, ideal conditions for their applications should be investigated. There are several reports on remediation potential of sunflowers (Dominguez-Rosado et al, 2004;Diab, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This information is important in the choice of the agents among their numerous species. Adapting P. ostreatus for use in the clean-up of petroleum-contaminated soils has been problematic (Stamet, 2005;Dickson et al, 2019). The present study also seeks to develop a realistic approach and investigate a novel substrate (Palm tree which is abundant in tropical regions) for application of P. ostreatus in the clean-up of petroleum-contaminated soils.…”
Section: Introductionmentioning
confidence: 99%